Mechanical and dynamic mechanical properties of natural rubber blended with waste rubber powder modified by both microwave and sol–gel method. Issue 4 (17th January 2013) - Luo, Mingchao; Liao, Xiaoxue; Liao, Shuangquan; Zhao, Yanfang
Abstract Waste rubber powder (WRP) was modified by microwave, sol–gel method, and both microwave and sol–gel method, respectively. The mechanical and dynamic mechanical properties of natural rubber (NR)/modified WRP composite were investigated. The influence of bis‐(3‐(triethoxysilyl)‐propyl)‐tetrasulfide (TESPT) content on curing characteristics and mechanical properties of vulcanizate was also studied. The results showed that NR/WRP modified by both microwave and sol–gel method composite owned the best mechanical properties. Rubber processing analyzer was used to characterize the interaction between silica and rubber chains and the dispersion of silica. With increase of TESPT content, the Payne effect decreased. Scanning electron microscopy indicated the coherency and homogeneity of in situ generated silica filled vulcanizate. Dynamic mechanical analyzer showed that NR/WRP modified by both microwave and sol–gel method composite with 5 phr TESPT exhibited the lower tan δ at temperature range of 50–80°C, compared with composite without TESPT and the higher tan δ at temperature of 0°C, compared with the conventional modification of WRP. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013